ТАSK FORCE FOR METHODOLOGY IN SUBJECT OF THE LOGIC - Ана Р. Кубурић (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2010)
This work represents a review of texts authored by those who have engaged in methodology of teaching logic in high schools from 1950' in former Yugoslavia and until today in Serbia. Besides several methodology textbooks in regards to teaching philosophy and logic, as well as several practical workbooks that contain logic assignments and expert studies, the work of those advocates has been recognizable in their workings through various journals. Some of those journals were methodological (if that sort of publications existed at a time), while others were philosophical and pedagogical. Considering that fact that such books are very few and the need for them is quite extensive, we have decided to collect all the information that we have been aware of so far and present a short introspective review of the concepts underlined in such works.